2015
DOI: 10.1016/j.jcin.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits Conferred by Radial Access for Cardiac Catheterization Are Offset by a Paradoxical Increase in the Rate of Vascular Access Site Complications With Femoral Access

Abstract: In a contemporary population where both RA and FA were used, the safety benefit associated with RA is offset by a paradoxical increase in VASCs among FA patients. The existence of this radial paradox should be taken into consideration, especially among trainees and default radial operators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 33 publications
1
56
0
1
Order By: Relevance
“…Similar limitations are encountered in other analyses that have described a Campeau paradox at the individual center level, where practice at the operator level were not considered. 19 While our analysis does not provide insight at the individual operator level whether changes in national practices toward radial have compromised femoral outcomes, our analysis suggests that at the center level changes in access site practice over time toward radial have not compromised femoral outcomes. Finally, while we find Radial Access and Femoral Outcomes in PCI no evidence of a Campeau paradox in the United Kingdom, our data might not be applicable to other healthcare systems in other countries.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Similar limitations are encountered in other analyses that have described a Campeau paradox at the individual center level, where practice at the operator level were not considered. 19 While our analysis does not provide insight at the individual operator level whether changes in national practices toward radial have compromised femoral outcomes, our analysis suggests that at the center level changes in access site practice over time toward radial have not compromised femoral outcomes. Finally, while we find Radial Access and Femoral Outcomes in PCI no evidence of a Campeau paradox in the United Kingdom, our data might not be applicable to other healthcare systems in other countries.…”
Section: Discussionmentioning
confidence: 73%
“…When the center transitioned from TFA to TRA and both approaches were used equally, they found that patients with TFA in the contemporary cohort experienced more vascular complications compared with patients with TFA in the historical cohort (unadjusted rates: 4.68% versus 2.89%; P<0.001; adjusted rates: 4.19% versus 1.98%; adjusted OR, 2.16; 95% CI, 1.67-2.81; P<0.001). 19 This difference was driven by a higher incidence of major hematoma (3.80% versus 1.24%; P<0.001) and retroperitoneal hematoma (0.22% versus 0.03%; P=0.002). This analysis was limited by the absence of pharmacological data, such as glycoprotein IIb/IIIa inhibitor use, anticoagulant use, concomitant femoral vein puncture (23.3% in contemporary cohort), and sheath size in the historical cohort.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…O presente estudo, que avaliou os dois procedimentos, encontrou uma incidência de 13,2% para complicações vasculares. Em uma coorte do Canadá, que também avaliou ambos os procedimentos, complicações vasculares foram relatadas em 3,18% dos casos [25]; no entanto, aquele estudo desconsiderou hematomas menores. No Brasil, Zukowski et al [26] avaliaram idosos submetidos à intervenção coronária percutânea e relataram uma taxa de 22,2% para hematomas.…”
Section: Discussionunclassified